2018
DOI: 10.1097/gox.0000000000002065
|View full text |Cite
|
Sign up to set email alerts
|

Beyond 30 Days: A Risk Calculator for Longer Term Outcomes of Prosthetic Breast Reconstruction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…The existence of a significant risk of complications (especially infectious) related to radiotherapy was shown by Jagsi et al (2016) and among the most common adverse effects, they mention an increased risk of wound infection between 7 and 24 months after sur-gery, and consequently the requirement to remove the implant. Similar observations were also presented by other authors (Momoh et al 2014;Blough et al 2018). In our work, the median time to remove the implant after using radiotherapy was 3-4 months after surgery.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The existence of a significant risk of complications (especially infectious) related to radiotherapy was shown by Jagsi et al (2016) and among the most common adverse effects, they mention an increased risk of wound infection between 7 and 24 months after sur-gery, and consequently the requirement to remove the implant. Similar observations were also presented by other authors (Momoh et al 2014;Blough et al 2018). In our work, the median time to remove the implant after using radiotherapy was 3-4 months after surgery.…”
supporting
confidence: 92%
“…In our study, this allowed the detection of approximately 90% of infections. The necessity to monitor for complications after breast reconstruction during one year after surgery, instead of 30 days, has also been indicated by other researchers (Blough et al 2018), who used individualized tools to assess the risk of post-surgery complications within one year of breast reconstruction.…”
mentioning
confidence: 99%
“…The length of follow-up is an important factor associated with reported SSI rates because most cases of implant removal do not occur within the first 30 days but later during the postoperative period, sometimes as late as 1 year after surgery . Cohen et al reported the median time to implant removal to be 41 days.…”
Section: Discussionmentioning
confidence: 99%
“…43 The length of follow-up is an important factor associated with reported SSI rates because most cases of implant removal do not occur within the first 30 days but later during the postoperative period, sometimes as late as 1 year after surgery. 11,19,[44][45][46] Cohen et al 47 reported the median time to implant removal to be 41 days. In their study, with a 12-month follow-up, 30 of 38 patients (80%) who lost their implant because of SSI did so within the first 6 months following surgery.…”
Section: Jama Network Open | Surgerymentioning
confidence: 99%
“…However, long-term complications that may be associated with mesh absorption like implant malposition or capsular contracture would not have been captured. 45 Our institution continues to collect data on a variety of techniques using this product for future analysis. Besides the foregoing discussion of intraoperative determination of prepectoral eligibility, we do not believe this study was subject to any specific selection bias, as the choice to use PDO mesh was presented to all patients eligible for immediate prosthetic breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%